Self-cleaning triboelectric nanogenerator based on TiO2 photocatalysis. (April 2020) - Liu, Hui; Feng, Yawei; Shao, Jiajia; Chen, Yao; Wang, Zhong Lin; Li, Hexing; Chen, Xiangyu; Bian, Zhenfeng
Abstract: Dielectric polymer materials are indispensable for the fabrication of self-powered nanosystem and electronic skin. However, the performance of the device is often seriously degraded due to the contamination of the surface. It is very important to keep the clean of the surface of the device, especially for the application of wearable devices. In this work, triboelectric nanogenerator (TENG) integrated with TiO2 photocatalysis is developed for realizing the dual functions of energy generation and self-cleaning interface. The friction layer of TENG is sponged polydimethylsiloxane (PDMS) film which is prepared by sacrificial template method with the pore size varied from hundreds of microns to several millimeters. When the interface of TENG is contaminated by organic pollutants, the open circuit voltage ( V OC ) of the device decrease from 125 V to 88 V. Under the solar illumination for 35 min, the self-cleaning interface can degrade the contaminants attached on the tribo-surface, while V OC raises from 88 V to 115 V after illumination, indicating that 92% of the TENG's output performance can be fully recovered. The photocatalysis-based self-cleaning effect on polymer tribo-material can contribute to the application of TENG towards e-skin and wearable devices. Graphical abstract: Image 1 Highlights: TENG with self-cleaning function can be used for its electrical performance recovery. Loading photocatalyst onto the surface of TENG device, its performance recovered to 90% under light irradiation. Due to the diversity of photocatalysts and dielectric materials, it is easy to apply to self-powered nanosystem.